THE EFFECTIVENESS OF STAR INSTRUCTIONAL MODEL IN TEACHING DESCRIPTIVE TEXT AT SEVENTH GRADE STUDENTS OF UPTD SMP NEGERI 4 PEMATANGSIANTAR - Bela Rosa Lumbanraja; Leonita Maria Efipanias Manihuruk; Siska Anggita Situmeang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this research was to find out whether the STAR (Select, Teach, Activate, and Revisit) instructional model had a significant effect on teaching descriptive text to the seventh-grade students of UPTD SMP Negeri 4 Pematangsiantar. This research employed a quantitative method with a quasi-experimental design. The sample consisted of 64 students taken from two classes. Class VII-1 was assigned as the experimental class and received treatment through the STAR instructional model, while class VII-4 served as the control class and was taught using the conventional method. The data were collected through a written essay test. The results showed that the mean score of the experimental class increased from 57.34 in the pre-test to 75.00 in the post-test, which was higher than the control class, which only improved from 58.90 to 66.09. At the significance level of α = 0.05 with a degree of freedom (df) of 64, the t-test result was greater than the t-table value (5.95 > 2.021). This indicates that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, it can be concluded that the STAR instructional model was effective in teaching descriptive tex.